Efecto del cilantro (Coriandrum sativum L) pulverizado como sustituto de la sal nitral en la calidad bromatológicas y microbiológicas en una bondiola curada - Palma Loor, Samantha Micaela (2025)
The objective of this research was to evaluate the partial substitution of sodium nitrite by pulverized coriander in the production of cured pork shoulder, analyzing its effects on the physicochemical and microbiological characteristics of the product; using a randomized experimental design with six treatments and three replications, allowing a robust and comparative evaluation between the different percentages of coriander. Cured pork shoulder was produced using different percentages of pulverized coriander (20, 40, 60, 80% and 100%) and various variables were evaluated (humidity, pH, fat, protein, nitrites and nitrates). In the physicochemical analysis, nitrite and nitrate levels in the pulverized coriander were found to be 7.29 and 8709.35 mg/kg respectively. In addition, variables such as humidity, fat and protein in the pork shoulder were measured following the corresponding NTE INEN regulations. The techniques used for the measurements were adequate: humidity by drying, fat by the Soxhlet method (NTE INEN 778), and protein by the Kjeldahl methodology (NTE INEN 781). The results indicated that the use of powdered coriander had a positive effect on the lipid profile (p_value < 0.000) and moisture retention of the cured pork shoulder; additionally, microbiological analyses confirmed the absence of pathogens such as Staphylococcus aureus, Clostridium perfringens and Salmonella, a relevant finding that supports the safety of the product. The inclusion of powdered coriander could be a viable alternative to improve the characteristics of cured pork shoulder while reducing the use of sodium nitrite.